Relative Age Effect in elite swimmers in U14 Czech Championship - Bozdech, M.; Agricola, A.; Krehký, A.; Schlegel, P.; Zhánel, J. (Studia Sportiva, 2022)
PURPOSE The issue of the Relative Age Effect (RAE) has been studied in the theory of sports for more than 30 years. Most studies concentrate on team sports, while the area of some individual sports like swimming can be considered still underexplored.